PEMIKIRAN PENDIDIKAN ISLAM KH.IMAM ZARKASYI - Rusli Takunas (Scolae: Journal of Pedagogy, 2018)
For Muslims in Indonesia in particular and Muslims in the Middle East and Southeast Asia in general, the existence of Pondok Modern Gontor Ponorogo, East Java is well known, through a number of graduates who have mastered Arabic and English well, and many of them are now become a national figure. The credibility of modern huts in producing such graduates is not separated from the role of figures who take part in it, KH. Imam Zarkasyi. The concepts applied in the effort to advance the cottage include education and teaching, regeneration, building, khizanatullah, and the welfare of the family of the hut. Broadly speaking, the concept of education renewal was carried out by KH. Imam Zarkasyi in the renewal of the pesantren education covers four areas, namely system updates and methods of education, material and curriculum, structure and management, mindset and freedom of education. Through the application of the concept of education, the existence of Gontor Ponorogo Modern Islamic Boarding Schools still exists and is sought after by the Islamic community.